Nowe Horyzonty . pismo młodzieżowe, no. 17, 1988 - Lubowlitański, Andrzej; Giertych, Jędrzej; Giertych, Maciej; Giertychowa, Maria; Lassus, Arnaud de; Seyda, Marian; Bohunowicz, Jerzy ([s.n.], 1988)
Creation and circulation: From issue no. 1=27(1991) published legally